Nitrogen and genotype effects on root growth and root survivorship of spring wheat. Issue 4 (26th June 2013) - Herrera, Juan M.; Noulas, Christos; Feil, Boy; Stamp, Peter; Liedgens, Markus
Abstract The nitrogen (N) fertilization of wheat (Triticum aestivum L.) is important for stable and high grain yield. However, the effect of N on root growth and survivorship is poorly understood. The objectives of this study were (1) to determine the effect of varying N availability on the growth and survivorship of roots and (2) to determine whether genotypic variation in N‐related traits are linked to root growth and survivorship. In a two‐year study, two spring wheat cultivars (Albis and Toronit) and an experimental line (L94491) were grown under low (20 kg N ha–1) and high N supply (270 kg N ha–1) in lysimeters equipped with minirhizotrons. The genotypes showed significant differences in N‐related traits: total shoot N content, grain N yield, N harvest index, and rate of decline in flag‐leaf greenness. However, there were relatively weak and inconsistent genotypic effects on the time course of root density, root growth during grain filling, and root survivorship. The level of N supply was the factor that most influenced the establishment, growth, and survivorship of roots; the high N supply, depending on the year and genotype, increased growth and survivorship of roots from 0% to 68% and 24% to 34%, respectively.